2007
DOI: 10.1074/jbc.m610901200
|View full text |Cite
|
Sign up to set email alerts
|

Neogenin-RGMa Signaling at the Growth Cone Is Bone Morphogenetic Protein-independent and Involves RhoA, ROCK, and PKC

Abstract: The repulsive guidance molecule RGMa has been shown to induce outgrowth inhibition of neurites by interacting with the transmembrane receptor neogenin. Here we show that RGMainduced growth cone collapse is mediated by activation of the small GTPase RhoA, its downstream effector Rho kinase and PKC. In contrast to DRG cultures from neogenin ؊/؊ mice, in which no RGMa-mediated growth cone collapse and activation of RhoA occurred, treatment of wild type DRG neurites with soluble RGMa led to a marked activation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 39 publications
(46 reference statements)
3
61
1
Order By: Relevance
“…In all cases, cell proliferation, migration and invasion were increased by neogenin-1 over-expression. Previously, it was reported that neogenin-1 regulates Rho/Rac/ROCK1 activity [35]. We reduced neogenin-1 expression, and then detected an associated decrease in both phosphorylated ROCK1 and total ROCK1 protein levels in AGS cells (Suppl.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…In all cases, cell proliferation, migration and invasion were increased by neogenin-1 over-expression. Previously, it was reported that neogenin-1 regulates Rho/Rac/ROCK1 activity [35]. We reduced neogenin-1 expression, and then detected an associated decrease in both phosphorylated ROCK1 and total ROCK1 protein levels in AGS cells (Suppl.…”
Section: Resultsmentioning
confidence: 59%
“…These data strongly suggest that over-expression of HSF-1 and galectin-3 jointly increases neogenin-1 expression both in vivo and in vitro . Neogenin-1 also appears to regulate gastric cancer cell motility through the activation of ROCK [35]. The function of ROCK1 is cell type-specific and remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that RGMa-induced growth cone collapse in DRG neurons is BMP-independent and acts via the GTP-RhoA signaling pathway (Conrad et al, 2007). Noggin also has no effect on RGMa-induced collapse response, further supporting the BMP signaling-independent nature of this phenomena (Conrad et al, 2007). …”
Section: Discussionmentioning
confidence: 99%
“…RGMb deletion decreases BMP signaling and inhibits early axonal regeneration in the sciatic nerve crush model [26]. In contrast, RGMa causes, by a BMPR-independent mechanism, growth cone collapse and neurite outgrowth inhibition by engaging the transmembrane receptor neogenin to activate the small GTPase RhoA and its downstream effectors Rho kinase and PKC [39]. Intrathecal administration of a blocking antibody against RGMa enhances CST regeneration and improves functional recovery [40].…”
Section: Bmp Signaling Regulates Cytoskeletal Dynamics During Axon Dementioning
confidence: 99%